ORANG MUDA BICARA TENTANG PENGARUH KOMUNIKASI BERBASIS KOMPUTER TERHADAP KEHIDUPAN UMAT BERIMAN - Yap Fu Lan (Jurnal Teologi (Journal of Theology), 2012)
This research explores young peoples perspective of the use of computer based communication and its influence to the meaning of human communication and to the life of religious communities. The method occupies focus group discussion, plain analysis, and narrative description. The young peoples speaking content three paradoxical pictures: extending human communication dissolves the personal aspect of it in a certain way; promoting virtual presence as the virtue of contemporary human communication, computer based communication corrupts the communal dimension of religious life; and giving hope to interreligious dialogue, computer based communication brings forth the concerns of religious leadership.